The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1051/0004-6361/201016100
|View full text |Cite
|
Sign up to set email alerts
|

An interesting candidate for isolated massive-star formation in the Small Magellanic Cloud

Abstract: Context. The region of the Small Magellanic Cloud (SMC) with which this paper is concerned contains the highest concentration of IRAS/Spitzer sources, H i emission, and molecular clouds in this neighboring galaxy. However, it has been the target of very few studies, despite this evidence of star formation. Aims. We present the first detailed study of the compact H ii region N33 in the SMC by placing it in a wider context of massive star formation. Moreover, we show that N33 is a particularly interesting candid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 84 publications
0
33
0
Order By: Relevance
“…Our investigation is the only observational study (apart from that presented by Selier et al 2011) that approaches the issue strictly from this perspective. Based on our findings we argue that panchromatic high-resolution observations in the vicinity of apparently isolated MYSOs (and not main-sequence stars) will allow a better understanding of the conditions and the parameters that set the stage for high-mass stars to form in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation is the only observational study (apart from that presented by Selier et al 2011) that approaches the issue strictly from this perspective. Based on our findings we argue that panchromatic high-resolution observations in the vicinity of apparently isolated MYSOs (and not main-sequence stars) will allow a better understanding of the conditions and the parameters that set the stage for high-mass stars to form in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their location and youth, these stars are good test cases to investigate whether massive stars can form in isolation (Zinnecker & Yorke 2007). Some compelling cases of likely isolated formation of massive stars have been reported in the Large (Chu & Gruendl 2008) and Small Magellanic Clouds (Selier et al 2011), and the fraction of actual isolated O stars in the Milky Way was assessed by de Wit et al (2004Wit et al ( , 2005 to be between 5% and 10%.…”
Section: Isolated O Stars In the Fieldmentioning
confidence: 99%
“…Core accretion models of massive stars on the contrary allow rather isolated O-stars to form (Krumholz et al 2009). Isolated O-type stars that are still in their formation region are surrounded by residual gas that can be seen through Hα observations (Lamb et al 2010;Selier et al 2011) and some of them are found in sparse clusters with less than ten lower-mass companions (Lamb et al 2010). Monte Carlo simulations by Lamb et al (2010) indicate that the existence of such sparse clusters is more in favour of the core accretion models and suggest that "clusters are built stochastically by randomly sampling stars from a universal initial mass function (IMF)".…”
Section: The Surroundings Of Hd 93521mentioning
confidence: 99%